Mixed model-based Jinks and Pooni method to predict segregating populations in wheat breeding - Mezzomo,Henrique Caletti (2021)
Abstract The improvement of superior wheat cultivars depends on the identification of promising segregating populations to derive superior lines. A lattice model (8×8) involving 56 F2 populations and eight parents was conducted in the 2020 cropping season, and grain yield per plant was evaluated for every F2 population, with further analysis of the population potential by Jinks and Pooni method via REML/BLUP. A total of 5,410 F2 plants were evaluated in this study. The results showed that the use of genetic variance associated with the individual genotypic value (BLUP) was superior compared with the use of variance and traditional phenotypic values. The F2 populations, CD 1303/BRS 254, CD 1303/Tbio Duque, CD 1303/Tbio Ponteiro, BRS 264/Tbio Aton, Tbio Ponteiro/Tbio Aton, and Tbio Sossego/CD 1303 had the highest likelihood of deriving superior lines.